Effects of the Business Cycle on Social Indicators in Latin America and the Caribbean : When Dreams Meet Reality - Vegh, Carlos A. (Washington, DC: World Bank, 2019)
After mediocre growth in 2018 of 0.7 percent. LAC is expected to perform only marginally better in 2019 (growth of 0.9 percent) followed by a much more solid growth of 2.1 percent in 2020. LAC will face both internal and external challenges during 2019. On the domestic front. the recession in Argentina; a slower than expected recovery in Brazil from the 2014-2015 recession, anemic growth in Mexico. and the continued deterioration of Venezuela. present the biggest challenges. On the external front. the sharp drop in net capital inflows to the region since early 2018 and the monetary policy normalization in the United States stand among the greatest perils. Furthermore, the recent increase in poverty in Brazil because of the recession points to the large effects that the business cycle may have on poverty. The core of this report argues that social indicators that are very sensitive to the business cycle may yield a highly misleading picture of permanent social gains in the region.